Seismic behavior of a partially grouted reinforced masonry structure: Shake‐table testing and numerical analyses. (10th May 2020) - Koutras, Andreas A.; Shing, P. Benson
Summary: In regions of low to moderate seismicity in North America, reinforced masonry structures are mostly partially grouted. The behavior of such structures under lateral seismic loads is complicated because of the interaction of the grouted and ungrouted masonry. As revealed in past experimental studies, the performance of partially grouted masonry (PGM) walls under in‐plane cyclic lateral loading is inferior to that of fully grouted walls. However, the dynamic behavior of a PGM wall system under severe seismic loads is not well understood. In this study, a full‐scale, one‐story, PGM building designed for a moderate seismic zone according to current code provisions was tested on a shake table. It was shown that the structure was able to develop an adequate base shear capacity and withstand two earthquake motions that had an effective intensity of two times the maximum considered earthquake with only moderate cracking in mortar joints. However, the structure eventually failed in a brittle manner in a subsequent motion that had a slightly lower effective intensity. A detailed finite element model of the test structure has been developed and validated. The model has been used to understand the distribution of the lateral force resistance among the wall components and to evaluate the shear‐strength equation given in the design code. The code equation has been found to be adequate for this structure. Furthermore, a parametric study conducted with the finite element model has shown that the introduction of a continuous bond beam right below a window opening is highly beneficial.